IMPLEMENTATION OF VISUAL POETIC ARCHITECTURE CONCEPTS IN CHURCH BUILDINGS - Olifian, Michael; Ratnasari, Anisza; Sawitri, Ida Ayu (Universitas Indraprasta PGRI, 2024)
Indonesia, which is located in a tropical climate zone, has great potential for utilizing sunlight in building design. Integrating natural lighting in building design, especially church buildings, not only supports the implementation of passive design but also adds to the aesthetics of the building. This study aims to review the application of the concept of poetic architecture from a visual aspect to church buildings. The method used is a literature review through exploration of precedent studies as case studies. Content analysis through within-case synthesis was carried out to explore how the application of natural lighting supports the concept of poetic architecture in church buildings. The research results show that the application of passive design not only increases visual comfort and energy efficiency, but also adds aesthetic value to church buildings. In this way, the church building not only fulfills functional needs but the church can also create a poetic and inspiring space.